AB1242 Comparing adherence to treatment in lupus and vasculitis patients. (12th June 2018) - Ntatsaki, E.; Ali, B.; Hamour, S.; Isenberg, D.; Salama, A.D.
Abstract : Background: Good adherence to prescribed pharmacotherapy is often over-estimated by physicians. Although in Systemic Lupus Erythematous (SLE) non-adherence is well-researched, 1 less research exists for vasculitis. Objectives: We compared cohorts of patients with SLE and vasculitis to identify emerging patterns, behaviours and differences that could introduce barriers to adherence. Methods: With patient input, we designed and undertook an anonymised questionnaire-based survey on the assessment of self-reported adherence and influencing factors in lupus and vasculitis clinics at University College Hospital (UCLH) and Royal Free Hospital (RFH). Both serve a largely urban and ethnically diverse population. Results: A total of 199 patients completed the questionnaire. 110 (55%) had lupus and 75 (38%) vasculitis. 14 (7%) patients reported having other conditions and thus excluded. 52% were Caucasian and 37% were born outside the UK. The majority (78%) were female and 28% were aged >60 years. Half were university graduates. Both centres had similar number of responses reducing bias. As shown in table 1, lupus patients were more females (p<0.001), younger (p<0.001), with longer disease duration (p<0.001) and commented that adherence decreased with time (p=0.011) compared to vasculitis patients. Conversely, the vasculitis patients had higher attendance at clinic appointments (p=0.022) and were more confident they could manage taking tablets correctly. 67% of lupus patients and 81% of vasculitis patients reported that they always took tablets as prescribed (p=0.104). Concerns of weight gain and osteoporosis worried patients on steroids. Changes in weight, appearance, nausea and fatigue were common side-effects for missed medications. A small number of patients cited religion or alternative therapies as a reason (<5%). Furthermore, as shown in fig 1, non-deliberate forgetfulness was the most common reason for non-adherence, in both groups. Overall, the majority of patients (96%) were self-medicating and reported taking an average of 5 different types of tablets, half of this for their Lupus/Vasculitis. Patients were well-informed about their condition and medications. Conclusions: Self-reported adherence was high in our cohort with differences between the two groups. "Forgetfulness" regarding medication and keeping track of hospital appointments were the commonest reasons for non-adherence rather than deliberate non-adherence. Therefore novel behavioural or electronic cues for medication, including mobile app use, and appointment alerts could lead to improvement. Further work is required to identify whether a different personalised approach in the lupus and vasculitis patients can improve adhrence. Reference: [1] Chambers SA, et al. Rheumatology. 2008;48: 266–271. Disclosure of Interest: None declared